2003
DOI: 10.1097/01.psy.0000088583.25140.9c
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Change in Hostility from College to Midlife in the UNC Alumni Heart Study Predict High-Risk Status

Abstract: High hostility in college and change in hostility from college to midlife predicts a full range of health risk indicators. When compared with the average population decline in hostility, gains in hostility at midlife are related to increased risk while declines in hostility are related to reduced risk. Higher midlife hostility is associated with increased odds of being in the higher risk group. Future research should focus on developing interventions to reduce hostility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 52 publications
3
74
0
3
Order By: Relevance
“…Furthermore, hostility may predict reduction in longevity and the increased likelihood of developing conditions such as hypertension and stroke (for a review, see Smith & MacKenzie, 2006). Hostility may also be associated with interpersonal and occupational problems, including greater discord in close relationships (Miller, Smith, Turner, Guijarro, & Hallet, 1996;Newton & Keicolt-Glaser, 1995;Smith, Pope, Saunders, Allred, & O'Keefe, 1998;Siegler et al, 2003), lower occupational status, and greater negative mood at work (Flory, Matthews, & Owens, 1998). It is possible that this interpersonal and occupational dysfunction may at least partially explain the finding that hostility is associated with depression risk (Ingram, Trenary, Odom, Berry, & Nelson, 2007).…”
Section: Sadness In the Diagnostic And Statistical Manual Of Mental mentioning
confidence: 99%
“…Furthermore, hostility may predict reduction in longevity and the increased likelihood of developing conditions such as hypertension and stroke (for a review, see Smith & MacKenzie, 2006). Hostility may also be associated with interpersonal and occupational problems, including greater discord in close relationships (Miller, Smith, Turner, Guijarro, & Hallet, 1996;Newton & Keicolt-Glaser, 1995;Smith, Pope, Saunders, Allred, & O'Keefe, 1998;Siegler et al, 2003), lower occupational status, and greater negative mood at work (Flory, Matthews, & Owens, 1998). It is possible that this interpersonal and occupational dysfunction may at least partially explain the finding that hostility is associated with depression risk (Ingram, Trenary, Odom, Berry, & Nelson, 2007).…”
Section: Sadness In the Diagnostic And Statistical Manual Of Mental mentioning
confidence: 99%
“…Anger can have a negative impact on interpersonal relations (11). High-anger individuals normally report more conflict with friends (12), have less social support (13), and are less satisfied with their current job and change their job more frequently (12).…”
Section: Introductionmentioning
confidence: 99%
“…The feeling of anger varies according to the way it is express (Arslan, 2010), and people may deal with or express their anger in various adaptive or maladaptive ways (Choi, Kim, Shin, & Cho, 2001), and unhealthy anger expression is linked to numerous physical and mental illnesses. Recent research has demonstrated a connection between anger, anger-related feelings, and increased risk for hypertension, cardiovascular disease (Lavoie, Miller, Conway, & Fleet, 2001), and for many other causes of morbidity and mortality (Siegler et al, 2003).…”
Section: Introductionmentioning
confidence: 99%